The spatial diffusion of a knowledge base: Laser technology research in West Germany, 1960-2005 - Michael Fritsch; Luis F. Medrano (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2010)
We analyze the spatial diffusion of knowledge in laser technology in West Germany from 1960, when this technology began, until 2005. Laser technology research has been nearly exclusively conducted in regions that are home to a university with a physics or electrical engineering department, an indication of the science-based character of the technology. Early adoption of laser knowledge was especially prevalent in large agglomerations. While we cannot detect knowledge spillovers from adjacent regions, geographic proximity to the center of initial laser research was conducive to early adoption of laser research; however, the effect is small. The earlier a region embarked on this type of research, the higher the level of laser research later, indicating the accumulation of knowledge generated in previous periods. Our results highlight the role of a region's absorptive capacity for commencing and conducting research in a new technological field. In the case of laser technology, it was more the level of existing tacit knowledge than an interregional transfer of tacit knowledge that played an important role.
Keywords: R11; O33; O52; 330; innovation; regional innovation systems; knowledge; spatial diffusion; laser technology; Laser; Wissenstransfer; Forschung; Räumliche Innovationsdiffusion; Deutschland